Legal Analysis of Bullying as a Crime of Psychological Violence - Naufal Wala, Gevan (Siber International Journal of Advanced Law (SIJAL), 2024)
This study analyzes bullying as a form of psychological violence from a legal perspective in Indonesia. Bullying, often overlooked compared to physical violence, poses serious threats to the mental and emotional well-being of victims. The research focuses on the legal definitions, types, and impacts of psychological bullying, particularly on children and adolescents. By reviewing relevant laws, such as the Child Protection Act and provisions in the Indonesian Penal Code (KUHP), the study highlights the legal frameworks that address bullying as a crime. The findings show that while existing regulations recognize psychological violence, there is still a need for stronger enforcement and awareness to prevent and mitigate bullying effectively. The study also emphasizes the importance of socialization, legal education, and psychological support for victims to build a safer environment for all, especially vulnerable groups.